2004
DOI: 10.1238/physica.regular.069a00441
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Hyperfine Structure of Ta I lines (VIII)

Abstract: The hyperfine structures of 57 new spectral lines of the tantalum atom were investigated by means of laser excitation. From the hyperfine patterns we have determined the angular momenta J; the magnetic hyperfine interaction constants A and the electric quadrupole interaction constants B of 15 new energy levels of even parity and three new levels of odd parity. The observation of laser-induced fluorescence led to the classification of further 156 spectral lines for the first time. Additionally 92 lines, observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Continuing our previous work concerning the tantalum atom (refs. [1][2][3][4][5][6][7][8]) we investigated the hyperfine (hf ) structure of a large number of previously unclassified spectral lines. Natural tantalum consists of two isotopes: 181 Ta (99.988%) and 180 Ta.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing our previous work concerning the tantalum atom (refs. [1][2][3][4][5][6][7][8]) we investigated the hyperfine (hf ) structure of a large number of previously unclassified spectral lines. Natural tantalum consists of two isotopes: 181 Ta (99.988%) and 180 Ta.…”
Section: Introductionmentioning
confidence: 99%
“…Zilio and Pickering [22] investigated an FT spectrum of Ta II and published hf constants of several levels. The FT spectrum taken by J. Pickering at Imperial College London and spectra taken at the Kitt Peak Observatory by Engleman Jr. were used later in Graz [8,23,24]. In these papers, the discovery of new energy levels of Ta I and the determination of hf constants of already known Ta I levels are reported.…”
Section: Ta IImentioning
confidence: 99%
“…Systematic investigations of the hyperfine (hf) structure of spectral lines of neutral tantalum have been performed by our international collaboration group since the beginning of the 1990s [1][2][3][4][5][6][7][8][9][10]. The main purpose of several first papers [1][2][3][4][5] was to determine the hf structure constants of already known levels, whereas later works [6][7][8][9][10] were devoted mainly to the search for unknown energy levels of the tantalum atom. During these investigations a great number of lines were classified and new energy levels were discovered.…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, a theoretical analysis of the even tantalum energy levels in the configuration space (5d + 6s) 5 [11] showed that the knowledge about the electronic structure of the tantalum atom was far from being complete at that time. But even after the discovery of a large number of even energy levels [6][7][8][9][10], most of them filling gaps in the mentioned theoretical prediction, predicted levels remain that have not yet been found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation